Protection measures for the Araucaria Forest and their efficiency in the conservation of Araucaria angustifolia in southern Brazil - Hess, André Felipe; Zanoello, Alice Rhoana; Liesenberg, Veraldo; Borsoi, Geedre Adriano; Stepka, Thiago Floriani; de-Sousa, Alex Nascimento; Costa, Emanuel Arnoni; Demétrio, Laryssa (Bosque (Valdivia), 2024)
Forests require sustainable management because of the long cycle of the species, the balance of the ecosystem, the structure or processes on which the species depend, and socioeconomic development. This study shows the effect of adopting protection measures (non-management and conservation) and their results on the forest structure of a Mixed Ombrophylous Forest, specifically for Araucaria angustifolia available in official publications and scientific articles. Bibliometric analysis was used to obtain and evaluate scientific publications based on their statistical methods, forest inventory techniques, modeling and, which contributed valuable information and scientific impact on the development of the topic. We argue that there are uncertainties about the threat of extinction and that lack of management may increase the disregard for forest resources. The losses of ecosystem services, economic structure, diversity, reproduction, and production of the forest due to non-use of resources are larger than the benefits.The results indicate the need for sustainable forest management as a public policy for the conservation of the species and the Mixed Ombrophilous Forest in southern Brazil.